Toward a Synthetic Access to Jatropha-5,12-dienes by Ring-Closing Metathesis: Detours and Dead-Ends - Butt, Lena; Schnabel, Christoph; Hiersemann, Martin (Synthesis, 2015)
Results from efforts aimed at the synthesis of polyhydroxylated jatropha-5,12-dienes are unveiled. An apparently pre-qualified plot consisting of successive aldol addition and ring-closing metathesis was pursued in order to construct the fully oxidized trans-bicyclo[10.3.0]pentadecane scaffold of naturally occurring jatrophanoids.
Keywords: terpenoids; total synthesis; aldol reaction; ring closure; metathesis